Body size, body norms and some unintended consequences of obesity intervention in the Pacific islands - Jessica Hardin; Amy K. McLennan; Alexandra Brewis (Taylor & Francis Group, 2018)
Background: Pacific Islanders have experienced over 50 years of obesity interventions-the longest of any region in the world. Yet, obesity-related non-communicable diseases (NCDs) continue to rise. 'Traditional' body norms have been cited as barriers to these interventions. Aim: In this study, we ask: 'What is the relationship between health interventions, body norms and people's experience of "fatness"? How - and why - have these changed over time?' We study two nations with high rates of obesity: Nauru and Samoa. Subjects and methods: Ethnographic fieldwork with people in everyday and clinical settings in Samoa (2011-2012; 2017) and Nauru (2010-2011). Results: Body norms are not a single or universal set of values. Instead, multiple cultural influences-including global health, local community members and global media-interact to create a complex landscape of contradictory body norms. Conclusions: Body norms and body size interventions exist in an iterative relationship. Our findings suggest that Pacific island obesity interventions do not fail because they conflict with local body norms; rather, they fail because they powerfully re-shape body norms in ways that confuse and counteract their intended purpose. Left unacknowledged, this appears to have (unintended) consequences for the success of anti-obesity interventions.